KETERWAKILAN PEREMPUAN DI PARLEMEN PADA PEMILU LEGISLATIF TAHUN 2024 DI KOTA MEDAN (STUDI KASUS DPD PARTAI GERINDRA) - GABRIELLA STEPANI; JULIA IVANNA (UIN Mataram, 2026)
The number of women participating in representations to reflect their conditions and positions is referred to as women's representation, as well as their self-esteem and development resources, for the benefit of society and the nation. However, women in their representation in the political world still have many obstacles, one of which is the patriarchal culture that is still inherent in the Indonesian state. This study aims to analyze the representation of women in the Gerindra Party in the 2024 Medan City legislative election, focusing on the case study of the Gerindra Party DPD. This research was carried out qualitatively with a descriptive approach, and data were analyzed through interviews and documentation. Data analysis consists of three stages: data reduction, data delivery, and data verification. The subjects of the study include the management of the North Sumatra Gerindra Party DPD and members of the Medan City Women's DPRD from the Gerindra Party. The results of the study show that women's representation in the Medan City Gerindra Party in the 2024 election has not reached the 30% target descriptively. However, substantive and transformative roles are beginning to evolve through party policies, training, and encouragement. The success of women's representation in the future depends on the synergy between individual readiness, party support, and cultural change in society.